2014
DOI: 10.2147/copd.s62886
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric capnography for the evaluation of chronic airways diseases

Abstract: BackgroundObstructive lung diseases of different etiologies present with progressive peripheral airway involvement. The peripheral airways, known as the silent lung zone, are not adequately evaluated with conventional function tests. The principle of gas washout has been used to detect pulmonary ventilation inhomogeneity and to estimate the location of the underlying disease process. Volumetric capnography (VC) analyzes the pattern of CO2 elimination as a function of expired volume.ObjectiveTo measure normaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
10
0
2
Order By: Relevance
“…AWD leads to increase in Slp3 compared to normal subjects. 38 In this study, the group with AWD presented Slp3 with higher values than the group with EMP, a fact which must reflect greater heterogeneity of gas distribution in the more peripheral airspaces of the lungs of the AWD group.…”
Section: Discussionmentioning
confidence: 49%
“…AWD leads to increase in Slp3 compared to normal subjects. 38 In this study, the group with AWD presented Slp3 with higher values than the group with EMP, a fact which must reflect greater heterogeneity of gas distribution in the more peripheral airspaces of the lungs of the AWD group.…”
Section: Discussionmentioning
confidence: 49%
“…The authors concluded that gas-elimination curves were not sufficiently sensitive to monitor the severity of structural abnormalities, although the normalized Phase III slope needed to be studied further as a sensitive index for detecting small-airway diseases in COPD patients. 38 In another study conducted in Brazil, Masiero et al evaluated perfused lung fraction in COPD patients using single-photon emission computed tomography. They observed that the lung-volume fraction that receives blood from the pulmonary artery was reduced in these patients and that the degree of underperfusion correlated with the FEV 1 :FVC value ( r =0597; P <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…, cystic fibrosis and noncystic fibrosis bronchiectasis [16][17][18] , asthma 19 , pulmonary embolism [20][21][22][23][24][25][26] .…”
Section: Resultsmentioning
confidence: 99%